2017
DOI: 10.1007/s12471-017-1006-z
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of antiplatelet treatment in patients undergoing isolated coronary artery bypass grafting in Dutch cardiothoracic centres

Abstract: Background International guidelines do not provide uniform recommendations regarding the use of antiplatelet treatment in the perioperative period in patients undergoing coronary artery bypass grafting (CABG). Methods A questionnaire was sent to all 16 cardiothoracic centres in the Netherlands to determine which antiplatelet treatment is used in the perioperative setting. Furthermore, a single-centre prospective observational cohort study was performed which included all patients undergoing isolated CABG in Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In this issue of the Netherlands Heart Journal, Janssen et al present the results of a survey amongst the cardiothoracic centres in the Netherlands on their strategies of perioperative antithrombotic therapy in CABG in the Netherlands [7]. The bottom line is that there is a large variation in the use of antithrombotic therapy around CABG, which was quite similar to the situation 27 years ago [8].…”
mentioning
confidence: 89%
“…In this issue of the Netherlands Heart Journal, Janssen et al present the results of a survey amongst the cardiothoracic centres in the Netherlands on their strategies of perioperative antithrombotic therapy in CABG in the Netherlands [7]. The bottom line is that there is a large variation in the use of antithrombotic therapy around CABG, which was quite similar to the situation 27 years ago [8].…”
mentioning
confidence: 89%
“…We included 17 studies (5 RCTs 28 , 29 , 30 , 31 , 32 and 12 cohorts 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ) that reported on 12,621 patients. The risk of bias for RCTs and cohort studies was low-to-moderate and moderate-to-high, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…MA ADP provides significant value by guiding the selection of surgical timing. Typically, for elective CABG, patients with MA ADP <35 mm should wait for more than 5 days before surgery; patients with MA ADP ranged 35 mm-50 mm should wait for 3–5 days prior to surgery; and patients with MA ADP >50 mm are allowed to receive the surgery on the same day as medication withdrawal ( 4 , 17 ). In the present study, no significant difference was observed when comparing the postoperative 24-h chest drains among the three TEG sub-groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, for patients scheduled for off-pump coronary artery bypass grafting (CABG), DAPT poses strong risk for perioperative bleeding in patients with CABG ( 3 ). Moreover, consumption of coagulation factor during cardiopulmonary bypass, dilution of fibrinogen and platelets, combined with other risk factors such as heparin and decreased body temperature, all result in depression on coagulation function, thus increasing the risk of perioperative bleeding, blood transfusion, postoperative mortality and rate of complication ( 4 ).…”
Section: Introductionmentioning
confidence: 99%